Improved two-photon polymerization through an optical fiber using coherent beam shaping. (January 2023) - Konstantinou, Georgia; Boniface, Antoine; Loterie, Damien; Kakkava, Eirini; Psaltis, Demetri; Moser, Christophe
Highlights: Three-dimensional microfabrication by two-photon polymerization is achieved through a multimode optical fiber by using wavefront shaping and the transmission matrix method. A microscope objective lens is bulky compared to an optical fiber, which is very thin and can access more easily confined areas for two-photon polymerization. Improving the smoothness of the structures fabricated with the fiber endo-printing system requires a characterization step and an efficient control of the flickering of the spatial light modulator. In the fiber endo-printer, the scanning and the size of the focused spot are controlled digitally, aiming smoother structures and faster scanning correspondingly. Abstract: The state of the art for high resolution three-dimensional light-based additive manufacturing mainly relies on two-photon polymerization. It consists of focusing and scanning a femtosecond laser beam on a photosensitive resin to initiate crosslinking and fabricate a 3D part. This is usually achieved with a bulky objective lens which prevents printing in confined spaces. Recently, it was proposed to replace it with a multimode fiber whose core diameter is 400 μm. Thanks to wavefront shaping it was shown that the refocused beam can be digitally scanned for two-photon 3D printing. This provided a new tool to deliver light in hard-to-reach places without any motion of the fiber distal end, but it requires multiple and fine calibration measurement with a relatively complex optical setup. Here, we go a step further and demonstrate a finer digital scanning method based on a transmission matrix approach. The latter is a faster and much easier method than previously reported techniques to manipulate light at the output of the fiber. In addition, it provides smaller hatching distances (down to 200 nm) which translates into smoother 3D printed structures and it also offers the possibility of engineering the focal spot size and shape. We demonstrate the fabrication of a woodpile structure with a focused beam size of 0.8 μm along x-y and 7 μm along z. The printing time for a layer is reduced from 29 minutes to 6 minutes by engineering the voxel shape which opens up new perspectives for high resolution, fast and smooth printing in confined areas.